Case Study Of Top Glove Corporation Berhad - Chee Mei, Heong (2010)
The general objective for this case study is to examine the real-life situations in an organizations in order to establish the future direction of the company in the short term basis by using the business analysis technique. This is very important for the organization in order to choose the right strategies to implement, instead of \"guesing\" or \"predicting\" woithout any techniques